Kansas Boy : the memoir of A.J. Bolinger - Bolinger, A. J. (Arthur Joel), 1881-1977; Barker, Jeffrey H., 1957-2021; Walker, Melissa (Lawrence, Kansas : University Press of Kansas, 2021)
"This is the childhood and early adulthood memoir of lawyer and judge A.J. (Arthur Joel) Bolinger (1881-1977), who was born and raised in Elk County, Kansas. Recounting cattle drives and ranching, farming, small-town life, college years at Topeka's Washburn University, and the beginning of his law career in Oklahoma, Bolinger's account provides a window through which modern readers can see how middle Americans experienced national events, from the Spanish-American War and the Populist Movement to presidential elections and temperance campaigns. Walker and Barker-the latter of whom is also Bolinger's grandson-have thoroughly annotated the memoir, substantiating it with research in family and historical archives and an introduction that gives an overview of Bolinger's life and places his story in the context of Kansas, Oklahoma, and American history"--
Background in general -- The town of thayer -- Early recollections -- We take a journey -- Fun on the farm -- The writing school -- New scenes and greener pastures -- The shape of things in little things -- Of politics and politicians -- Opening the Indian lands -- Social life in a small town -- Life in Topeka -- The era of change -- The birth of a new commonwealth -- Journey's end.
Online resource; title from digital title page (viewed on July 09, 2021).
JSTOR
Keywords: Bolinger, A. J. -- 1881-1977.; Bolinger, A. J. -- 1881-1977.; Lawyers -- United States -- Biography; Judges -- United States -- Biography; Avocats -- États-Unis -- Biographies; Juges -- États-Unis -- Biographies; Personal Memoirs; BIOGRAPHY & AUTOBIOGRAPHY; 19th Century; United States; HISTORY; State & Local; Lawyers; Judges; United States; Electronic books; collective biographies; autobiographies (literary genre); Autobiographies; Biographies; Autobiographies; Biographies; Autobiographies; Biographies